Pengaruh Islamic Marketing Mix terhadap Kepuasan Tamu pada Hotel Syariah Grand Bunda Kota Bukittinggi - Dadly Rayhan Alfattah; Arif Adrian (Pusat Riset dan Inovasi Nasional, 2024)
This research is motivated by guest complaints at the Syariah Grand Bunda Bukittinggi Hotel which affect guest satisfaction, as well as the low occupancy rate. This study aims to determine the effect of Islamic Marketing Mix (pragmatism, pertinence, palliation, peer-support, pedagogy, persistence, and patience) on guest satisfaction at the Syariah Grand Bunda Bukittinggi Hotel. The method used in this study is a quantitative method. Using primary data through the distribution of questionnaires with a total of 45 statements to 96 respondents. Using purposive sampling technique. Data analysis conducted is multiple regression analysis with the help of the SPSS program version 23.00. The results of this study indicate that all Islamic Marketing Mix variables simultaneously have a significant effect on guest satisfaction at the Syariah Grand Bunda Bukittinggi Hotel. Partially shows that the variables of pragmatism, pedagogy, and patience have a significant positive effect on guest satisfaction at the Syariah Grand Bunda Bukittingi Hotel, while the variables of pertinence, palliation, peer-support, and persistence do not have a significant effect on guest satisfaction at the Syariah Grand Bunda Bukittinggi Hotel. Based on the research results, it is recommended to improve the Islamic Marketing Mix to achieve guest satisfaction.